School enrolment and attendance of Indigenous children: An analysis using Footprints in Time data - Yu, Peng (My University, 2015)
This research investigates school engagement of Indigenous children in Australia using a unique longitudinal dataset of Indigenous children. School enrolment generally seems not to be a big concern; virtually all the study children were enrolled in school by age six or seven. However, a (slight) delay in enrolment is associated with lasting socioeconomic disadvantages such as poor parental education and non-employment, low family income and reliance on government benefits. School attendance is more challenging than enrolment; up to 19% of the study children were absent from school at least one day in the week prior to interview. The reasons appear more complex and related to less persisting factors such as child health, sleeping issues and family financial difficulties. The results also highlight the importance of school related factors such as relationships with teachers and peers and indicate a risk of establishing a pattern of absence at an early stage.
Keywords: Children -- Indigenous; Children -- School age; Relationships -- Formation; Families and relationships; Relationships; Children; Indigenous; Formation; School age; Families and relationships